Pendampingan Penjaminan Mutu Pendidikan Anak Usia Dini Melalui Sosialisasi Instrument Akreditasi - Ghofur, Abd.; Suryanto, Hadi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
The activity was conducted at the Lamongan district education office hall and involved 50 education units. The activity was conducted through lecture mode and reflection of education units with accreditation instruments. From the socialisation activities, it was found that some education units still do not understand the quality assurance of education through accreditation, the diversity of the level of understanding of education quality assurance has an impact on the implementation of learning carried out is still not in accordance with national education standards. The need to improve the quality of education through accreditation instruments is expected to implement learning objectives as expected.